2006
DOI: 10.1164/rccm.200605-721oc
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Ubiquitin–Proteasome Pathway in the Diaphragm in Chronic Obstructive Pulmonary Disease

Abstract: Rationale: Studies show that the myosin content of the diaphragm in patients with mild to moderate chronic obstructive pulmonary disease (COPD) is reduced, compromising diaphragm contractile performance. The mechanisms for reduced contractile protein content are unknown. In the present study we hypothesized that the loss of contractile protein content is associated with activation of the ubiquitin-proteasome pathway in the diaphragm of patients with mild to moderate COPD. Methods: Proteolytic activity of isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
118
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 51 publications
12
118
2
1
Order By: Relevance
“…Unlike animal experiments, studies on diaphragm fibers from human COPD patients exhibit elevations in caspase-3 activity (67). They also reveal increased 20s proteosome activity and elevated levels of atrogin-1, an E-3 ligase, believed to be involved with the regulation of protein ubiquitination in atrophic muscles (67). Ubiquitination is one of the first steps in degrading damaged proteins via the proteosome or in tagging proteins targeted for degradation in the process of atrophy or fiber shortening.…”
Section: Evidence For Respiratory Muscle Injury Protein Degradationmentioning
confidence: 99%
“…Unlike animal experiments, studies on diaphragm fibers from human COPD patients exhibit elevations in caspase-3 activity (67). They also reveal increased 20s proteosome activity and elevated levels of atrogin-1, an E-3 ligase, believed to be involved with the regulation of protein ubiquitination in atrophic muscles (67). Ubiquitination is one of the first steps in degrading damaged proteins via the proteosome or in tagging proteins targeted for degradation in the process of atrophy or fiber shortening.…”
Section: Evidence For Respiratory Muscle Injury Protein Degradationmentioning
confidence: 99%
“…In Figure 4b the genes involved in this pathway are highlighted from the rest of the other genes, which total to 17 out of 1667 in the gene set. In previous studies, the ubiquitin protease degradation pathway has been associated with COPD (Ottenheijm et al, 2006).…”
Section: Known and Novel Targetsmentioning
confidence: 93%
“…However, treadmill training reduced the expression of these genes in all exercised groups, a fact that could be beneficial in cachexia and disuse conditions. Recent studies have shown an increase of molecular markers of muscle atrophy in human COPD (8,9). Doucet and colleagues (8) reported an increase in the activation of muscle atrophy by the up-regulation of atrogin-1 and MuRF1 in the quadriceps muscle of COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…www.bjournal.com.br Doucet and colleagues (8) reported an increase in atrogin-1 and MuRF1 (232 and 517%, respectively) mRNA in the quadriceps muscle of patients with COPD. Furthermore, Ottenheijm et al (9) also showed an increase in atrogin-1 gene expression in the diaphragm muscle of patients with mild to moderate COPD. Atrogin-1 and MuRF1 mRNA levels are reliable molecular markers for muscle atrophy by being increased substantially in peripheral skeletal muscle in various muscle-wasting conditions, such as denervation, immobilization, cancer, sepsis, and aging (10)(11)(12).…”
Section: Introductionmentioning
confidence: 94%